Peran Green Banking dalam Meningkatkan Loyalitas Nasabah Bank Syari’ah - Widia Rahmadani; Muhammad Iqbal Fasa (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2025)
Amid increasingly alarming global warming issues, environmental degradation is not only an ecological concern but also involves economic and social aspects. The banking sector, particularly Islamic banking, holds significant potential to contribute to promoting sustainable and environmentally friendly practices. One concrete effort that can be made is through the implementation of the Green Banking concept. This concept integrates sustainability principles into every aspect of banking operations. The implementation of greener banking practices not only has a positive impact on environmental preservation but also offers advantages in terms of greater operational efficiency, reduced operational costs, and the strengthening of the bank's positive image in the eyes of customers. This study aims to analyze the role of Green Banking as a supporting factor in enhancing customer loyalty, particularly in the Islamic banking industry sector. The study is conducted using a qualitative approach with a descriptive method. The results of this research are expected to serve as recommendations for the banking sector in developing strategies to enhance customer loyalty through Green Banking indicators.